A cross-sectional study on incidence and indications for induction of labor and the factors associated with failure of induction - Kalpana N,; Manvi MR, (Asian Journal of Medical Sciences, 2024)
Background: Induction fails in about 20% of induced pregnancies and has no universally accepted definition. Failed induction is the failure to establish labor or inability to achieve the active stage of labor, considering the definition of induction of labor (IOL). It needs to be differentiated from the failure of progress of labor. There is no evidence to recommend treatment for failed induction, but usually, delivery by cesarean section will be required. Aims and Objectives: The study was designed to start induction for an indication that justifies operative delivery in cases of failure. Materials and Methods: A prospective observational study was done over a period of 1 year among antenatal women confirmed to be at term with cephalic presentation in the absence of active labor with unscarred uterus. Results: The incidence of IOL was found to be 25.97% and failure was observed in 50 (21.83%) of those included in the study. Among those with failure, failed pre-induction ripening was seen in 26 (11.3%) and failed induction in 24 (10.4%). Although many variables were found to be associated with the outcome of labor, a statistically significant association was observed with premature rupture of membranes, pre-induction Bishop score, and birth weight of the baby. Conclusion: The study helps in better clinical judgment of patients who will have a successful induction or a failed induction and the patients could be counseled accordingly. This judgment will also help to avoid unnecessary inductions in those who have the risk factors for failed induction unless the induction is absolutely necessary.